Emojis In Digital Communication: A Semiological Study Following Roland Barthes’ Framework (مجلة الواحات للبحوث والدراسات, 2026)
This study investigates the semiotic dimensions of emojis in digital communication, questioning whether they function as a universal visual language. Using Roland Barthes’ three levels of signification—denotation, connotation, and myth—the research analyzes a purposive sample of ten frequently used emojis, categorized into emotional expressions, gestural signs, and cultural objects. Findings show that while emojis present relatively stable denotative meanings, their connotative and mythic interpretations vary widely depending on cultural and social contexts. At the mythic level, emojis reproduce ideologies of emotional transparency, positivity, consumerism, and gender norms, challenging the assumption of universality. By applying Barthes’ framework holistically, the study contributes to emoji scholarship and emphasizes the importance of semiotic inquiry in understanding digital discourse. Future research is encouraged to adopt cross-cultural and comparative approaches in order to capture the complex and evolving nature of emoji usage.